2021
DOI: 10.3389/fphar.2021.664500
|View full text |Cite
|
Sign up to set email alerts
|

An Ethnobotanical Study of Medicinal Plants in Mersin (Turkey)

Abstract: This comprehensive ethnobotanical study carried out in Mersin province, which is located in the southern part of Anatolia, east of the Mediterranean Sea, compiles details on plants used in folk medicine and ethnopharmacological information obtained through face-to-face interviews. The aim was to collect and identify plants used for therapeutic purposes by local people and to record information on traditional herbal medicine. Plant specimens were collected in numerous excursions. Additionally, informant consens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 77 publications
2
13
0
Order By: Relevance
“…This study revealed that the family Lamiaceae has contributed the highest medicinal plant diversity, followed by Asteraceae and Solanaceae. These families are among the top plant families with contributing the largest medicinal plant species as reported from other parts of Ethiopia [ 8 , 9 , 18 , 24 ] and elsewhere in the world [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that the family Lamiaceae has contributed the highest medicinal plant diversity, followed by Asteraceae and Solanaceae. These families are among the top plant families with contributing the largest medicinal plant species as reported from other parts of Ethiopia [ 8 , 9 , 18 , 24 ] and elsewhere in the world [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gentianaceae ES/H/B Common centaury/Tukul otu, kırmızı kantaron Stomach pains, gastritis, ulcers, indigestion and loss of appetite [ 28 , 44 ] Çevlik 7 Cephalaria syriaca (L.) Schrad. Caprifoliaceae IN/Th/A Cephalaria/Pelemir Antimicrobial, antioxidant, sedative, antidiabetic, analgesic,.seeds are mixed with bread flour for flavor in the baking industry, in leather business [ 45 47 ] Yayladağı 8 Cistus creticus L. Cistaceae ES/Ch/P Pink rock-rose, hoary rock-rose/Karağan, laden For constipation, diabetes, as cardiovascular, nutritional, digestive, stimulant, expectorant, antifungal, astringent [ 28 , 48 50 ] Kızıldağ 9 Cynoglossum creticum Mill. Boraginaceae IR/H/B Dog’s tongue/Köpek dili Emollient, hydrated burns, wart treatment, antitumoral and antispasmotic [ 51 , 52 ] Arsuz 10 Daphne sericea Vahl Thymelaeaceae M/Ph/P Daphne/Develik otu Toothache, rheumatic pain, malaria and blood cancer, ulcer, skin diseases, menstruation, as diuretic, diaphoretic, used in broom construction.…”
Section: Methodsmentioning
confidence: 99%
“…A decoction made with the roots was an excellent remedy to treat many affections such as cough, sore throat, stomach ache, toothache, menstrual pain, hypertension, dermatitis, and weakness. In other countries, such as the Iberian Peninsula and Turkey, mallow was also used as an antipyretic [ 92 ] and for abdominal pain [ 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hypericum perforatum L. (CI 0.61, UI 1.00). Hypericum flowers were widely used in phytotherapy, not only in Italy but all over the world [ 93 , 96 , 100 , 101 ]. An infusion to aid digestion, as a cholagogue and anti-depressant, to treat constipation and sleep disorders, with relaxing properties is used.…”
Section: Resultsmentioning
confidence: 99%